Analisis Faktor Kesulitan Belajar Siswa Mata Pelajaran Pembuatan Busana Kerja Kelas XII Tata Busana SMK NU 2 Blawirejo Kedungpring - Dyah Ayu Vimastuti; Imami Arum Tri Rahayu; Peppy Mayasari; Mita Yuniati (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This study aims to determine (1) the learning difficulties experienced by students in the competence of making work clothes in class XII Cosmetology SMK NU 2 Blawirejo Kedungpring in terms of; a) Affective aspects b) Cognitive aspects c) Psychomotor aspects. (2) the most dominant factor of learning difficulties in the subject of making work clothes in class XII SMK NU 2 Blawirejo Kedungpring from; a) Affective aspects b) Cognitive aspects c) Psychomotor aspects This research is descriptive research. This research was conducted in the odd semester of the 2023/2024 academic year at SMK NU 2 Blawirejo Kedungpring. The population used in this study were 18 students. The data collection technique used a questionnaire with a guttman scale. The results showed that (1) the learning difficulties experienced by students were as follows: (1) the learning difficulties experienced by students are as follows: (2) the most dominant factor of learning difficulties in making work clothes is the cognitive factor, which is included in the high category, namely 12 (69%) experiencing difficulties and the psychomotor aspect is included in the high category, namely 12 (67%) experiencing difficulties (2) the most dominant factor of learning difficulties in making work clothes is the cognitive factor.